Angiolymphoid Hyperplasia with Eosinophillia - A Rare Entity - N,, Tariq; S,, Sadiq; SI, Kehar (International Journal of Pathology, 2018)
Objectives: To Know the frequency of angiolymphoid hyperplasia with eosinophilia.Study Design: Cross sectional.Material and Methods: Retrospective cases were retrieved from the files of basic Medical Science Institute, of JPMC, overa period of 9 years (2000-2001).Results: Only 8 cases were reported over a period of 9 years giving an average of one case every 13 months confirming therarity of occurrence of this lesion. Maximum cases of ALHE were seen between 21-30 year. The lesion was found morecommonly in males with 7 cases and only one female. 75% of the lesion in our study was in the head and neck region similarto the Western studies 8.3% cases were seen in abdomen 8.3% in the back and 8.3% in the vessels. One case was seen arisingwithin the radial artery. In all our cases small & medium sized vessels were involved with plump endothelial cells. Cellularcomponent comprising of lymphocytes, histiocytes & eosinophils were seen in almost all reported cases. However lymphoidfollicle was seen in only one case.Conclusion: It is an unusual benign vascular tumour, it is seen predominantly among Asians than in Whites, morecommon in young males in second to third decades. Clinically the lesions affects the scalp, face, ears and periauricular area aswell as the neck. Peripheral blood eosinophilia and lymphadenopatly is usually associated together ALHE is marked byproliferation of blood vessels with distinctive, large endothelial cells. These blood vessels are accompanied by characteristicinflammatory infiltrate that includes eosinophils. Intra vascular forms of this tumour are also of note